Therapeutic dilemma in the management of a patient with the clinical picture of TTP and severe B12 deficiency. Issue 1 (December 2015) - Walter, Kara; Vaughn, Jennifer; Martin, Daniel
Abstract Background Idiopathic thrombotic thrombocytopenic purpura (TTP) is a rare hematological emergency characterized by the pentad of microangiopathic hemolytic anemia, thrombocytopenia, neurological symptoms, renal injury, and fever that is invariably fatal if left untreated. Prompt intervention with plasma exchange minimizes mortality and is the cornerstone of therapy. Rare reports have described "pseudo-TTP" driven by extreme hematologic abnormalities resulting from deficiency of vitamin B12 . Distinguishing between these entities can pose a diagnostic and therapeutic challenge. Case presentation A 77 year old female presented with altered mental status, renal insufficiency, thrombocytopenia and evidence of microangiopathic hemolytic anemia, suggesting TTP. Workup demonstrated macrocytosis and reticulocytopenia, and B12 level was unmeasurably low. Other elements of her clinical presentation, including volume loss and bleeding suggested a multifactorial pathogenesis could be contributing to her laboratory abnormalities, reducing the likelihood that she had TTP. The risks and benefits of treating aggressively with therapeutic plasma exchange (TPE) for TTP were considered given the diagnostic possibilities. The patient received TPE initially, with rapid de-escalation after her clinical response suggested "pseudo-TTP" from B12 deficiency was the driving the process. B12 supplementation corrected her hematologic abnormalities and she remains well two years after presenting. Conclusions TTP is a rare condition with fatal consequences if left untreated. Guidelines recommend TPE even if there is uncertainty about the diagnosis of TTP. B12 deficiency is common, though not typically associated with severe hematologic abnormalities. We compare the presenting characteristics of all thirteen cases of pseudo-TTP reported in the literature with those from patients in case series of TTP to suggest a set of parameters that can help clinicians distinguish between pseudo-TTP and TTP and guide decision making regarding intervention. Evaluation of all TTP cases should include a B12, methylmalonic acid level and reticulocyte count. Reticulocytopenia suggests B12 deficiency. Finally an LDH level above 2500 IU/L is relatively uncommon in TTP and should suggest consideration of B12 deficiency.